2016
DOI: 10.21475/ajcs.2016.10.03.p6465
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supply affects root and shoot amino acid composition in Eucalyptus clones

Abstract: Changes in amino acid composition are frequently observed in plants under various conditions of stress, such as nutrient deficiencies. Hence, amino acids have been proposed as more sensitive indicators of N status than total N concentration. The goal of this study was to evaluate alterations in amino acid composition of young eucalyptus clones as a result of variable N supply. An experiment was carried out in a greenhouse with two Eucalyptus clones (VM-01 and I-144) and six N application rates (0, 0.74, 2.93, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…At the same time, the total N content remained unchanged (S7 Table). This is in line with observations made by Ferreira, Novais (18), who concluded that free-amino acids show a greater promise than total N in understanding the effect of external N on the plant N status, in that amino acid content can respectively increase or decrease in stress conditions without any changes in the total N. Although no studies could be found on the effect of external N on amino acid profile in legumes, (31) reported a decrease in the content of non-essential amino acids in response to high N for maize (Zea mays L.). They hypothesized that decline of the non-essential amino acids was due to deficiency of carbon skeletons for the assimilation of NH 4 + .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…At the same time, the total N content remained unchanged (S7 Table). This is in line with observations made by Ferreira, Novais (18), who concluded that free-amino acids show a greater promise than total N in understanding the effect of external N on the plant N status, in that amino acid content can respectively increase or decrease in stress conditions without any changes in the total N. Although no studies could be found on the effect of external N on amino acid profile in legumes, (31) reported a decrease in the content of non-essential amino acids in response to high N for maize (Zea mays L.). They hypothesized that decline of the non-essential amino acids was due to deficiency of carbon skeletons for the assimilation of NH 4 + .…”
Section: Discussionsupporting
confidence: 94%
“…In that context our findings support that not only the amount of amino acids, but also information on the composition of amino acids is needed to determine to what extent the plant is N stressed and how the plant signals N demand between root and shoot. Thus, our findings demonstrate that the external organic and inorganic N affects the accumulation of certain amino acids in clover, which could help in further understanding how the plant senses various N stress conditions and circulates amino acids between roots and shoots (18, 32). Soil inorganic and organic N status could therefore be used as an indicator for nutritional quality of protein content in forage legumes.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As a result, NH 4 + toxicity decreases shoot and root dry mass production ( Fig 3 ). On the other hand, N supply at low levels decreases dry mass production ( Fig 3 ), due to the important function of this nutrient in plant metabolism, which also occurs in eucalyptus seedlings [ 3 ].…”
Section: Discussionmentioning
confidence: 99%